2005
DOI: 10.3346/jkms.2005.20.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Differentially Expressed in the Conventional Renal Cell Carcinoma by Proteomic Analysis

Abstract: Renal cell carcinoma (RCC) is one of the most malignant tumors in urology, and due to its insidious onset patients frequently have advanced disease at the time of clinical presentation. Thus, early detection is crucial in management of RCC. To identify tumor specific proteins of RCC, we employed proteomic analysis. We prepared proteins from conventional RCC and the corresponding normal kidney tissues from seven patients with conventional RCC. The expression of proteins was determined by silver stain after two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Although the ketohexokinase is mostly abundant in liver, it was also found in kidney, small intestine and pancreas (4). Hwa et al (4) found lower levels of ketohexokinase in ccRCC tissues, in accordance with our findings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although the ketohexokinase is mostly abundant in liver, it was also found in kidney, small intestine and pancreas (4). Hwa et al (4) found lower levels of ketohexokinase in ccRCC tissues, in accordance with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Since then, other studies were performed with the same goal under different conditions or different proteomics approaches (3)(4)(5)(6)(7)(8). The method that was applied in this study is based on 2DE, the most traditional technology for separation of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 However, it has been reported that ECHS1 expression is decreased in renal cell carcinomas 35 and in hepatocellular carcinomas. 36 This most likely indicates that alterations in fatty acid metabolism pathways vary among PCa and other cancers.…”
mentioning
confidence: 99%
“…We will not review this area in great depth but will use examples of specific techniques that have been used. A number of studies have used 2D gels to compare proteins expressed in tumors to normal tissue (10,51,61,100,101,104).…”
Section: Urological Cancersmentioning
confidence: 99%